O-EGS06 Trials and Tribulations: Educational Impact and Recommendations from the Implementation of Student-Led Recruitment in a Clinical Trial. (16th December 2021) - Cambridge, William; Riad, Aya; Henshall, David; McAdam, Heather; Glasbey, James; Harrison, Ewen; McLean, Kenneth
Abstract: Background: Medical students have an essential role in medical research, yet often feel unprepared and lack opportunities for involvement as recruiters within research studies. This study aimed to understand the educational effect of involvement in clinical trial recruitment on medical students, and to derive generalisable future recommendations. Methods: Tracking wound infection with smartphone technology (TWIST) was a randomised controlled trial enrolling adult emergency abdominal surgery patients across two university teaching hospitals. All recruiters underwent pre-recruitment training based on "Generating Student Recruiters for Randomised Trials" (GRANULE) principles, and completed pre-and post-recruitment surveys. Respondent agreement with statements were assessed using 5-point Likert scales (from 1 ["strongly disagree"] to 5 ["strongly agree"]). Quantitative data were analysed using paired t-tests to compare differences pre- and post-involvement, and a thematic analysis approach adopted for anonymised free-text answers. Results: Of 492 patients recruited to TWIST from 2016 to 2020, 86.0% (n = 423) were recruited by medical students. Following student involvement, the monthly recruitment rate tripled (4.8 to 15.7 patients). Thirty student recruiters (96.8%), completed both surveys, reporting significant improvements in clinical and academic competencies. This included increased confidence in gaining and documenting consent, as well as interest in pursuing a clinical-academic career. Over half (58.2%) felt the undergraduate curriculum had not prepared them for involvement in clinical trials (mean:2.47, SD: 0.94). There were three emergent themes regarding recommendations for involvement of students, based on their engagement, preparation, and support during recruitment. Conclusions: Student recruitment in clinical trials is feasible and provides a route to developing a research-active medical workforce. It also accelerates recruitment to clinical trials, as well as benefiting students through development of clinical competencies and provision of additional exposure to research. Adequate training, support, and selection of suitable trials are essential for successful student engagement.